(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The Iberian writing system is set in a mixed syllabic and alphabetical order. The Iberian signs don’t form a monumental writing, but they are a type of funeral, figurative and administrative or religious writing. The cultural level of this notarial activity spontaneously drove at a homogeinity of the proceedings and the criterions among the scribes: certainly the (hemisyllabical) writing was one of the cohesion’s factors in the Iberian world. The Iberian ypm:pt:úc, when he had to note one open syllabe with initial consonantical group or one joined syllabe with consonant or with initial vowel (provided he didn’t make use of the Jonian alphabet), he cans turn to different resources and for this case he was bound to use syllabic signs (in the case with occlusives) with dead vowel. When in a text in hemisyllabic writing appears a sequence without occlusives, this type of writing really acts as alphabetical writing.